ANALISIS MODEL PEMBELAJARAN PjBL DALAM MEMBANGUN PEMBELAJARAN MATEMATIKA DAN PENERAPAN P5 PADA KURIKULUM MERDEKA - Siratul Kholifah; Ahmad Yani T (Universitas Bhinneka PGRI, 2024)
The research, which focuses on Project Based Learning (PjBL), aims to foster character and learning independence in students and still refers to the Pancasila Student Profile. This study uses a qualitative descriptive methodology. The sample in this study was taken using non-probability sampling techniques. In accordance with the findings of the research using a project-based learning model, the initiative to improve the profile of Pancasila students at SMP Negeri 3 Sungai Pinyuh was carried out with a project-based learning model. This can be seen from the activities in the P5 activity with the theme of Local Wisdom, namely the manufacture of West Kalimantan's typical food, Spicy Porridge. In addition, the Project Based Learning learning model can be applied to mathematics learning as a novelty in mathematics learning, namely the creation of posters for grade VII ratio materials